Transfer Teknologi Pengayaan Bibit Rumput Laut Yang Dibudidayakan Dengan Keramba Jaring Apung - Ni Putu Dian Kusuma; Zainal Usman; Winardi Winardi; Hidayat Ali; Ellysabet M. A. Betty; Maria D. Banase; Putri C. J. Olla (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2023)
Inappropriate cultivation methods and a decrease in the quality of seaweed seeds are some of the obstacles in seaweed production. Technology transfer activities through community service programs aim to provide learning to seaweed farmers on how to enrich seaweed seeds with bionic fertilizer and then cultivate them using the floating net cage method. The activity was carried out on August 24-25, 2022 at the Main Base Command Headquarters of the Indonesian Navy VII Kupang. The method used was a participatory empowerment approach involving seaweed farming communities with counseling and dissemination. Seaweed cultivation with the floating net cage method showed higher absolute growth, relative growth and daily growth rate compared to the longline method, which were 11.91 ± 0.69 g day-1, 0.032 ± 0.002 g g-1 day-1 and 3.14 ± 0.17% day -1, respectively. While in the longline method, it was 9.48±1.81 g day-1, 0.027±0.004 g g-1 day-1, and 2.65±0.43% day -1, respectively.